Exterior material for power storage device, manufacturing method thereof, and method for selecting sealant film to be used as sealant layer in exterior material for power storage device
The laminated exterior material for power storage devices, featuring a specific sealant layer with defined dynamic viscoelastic properties, addresses the heat resistance issues of existing materials, ensuring robust seal strength at both room and high temperatures.
Patent Information
- Application Number
- JP2019238450
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2019-12-27
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2039-12-27
AI Technical Summary
The existing laminated exterior materials for lithium-ion batteries lack sufficient heat resistance, leading to inadequate packaging of all-solid-state batteries when used at high temperatures.
A laminated exterior material structure comprising a substrate layer, a barrier layer, and a sealant layer, where the sealant layer exhibits specific dynamic viscoelastic properties, including subdispersion and main dispersion peaks within defined temperature ranges, enhancing both high-temperature seal strength and initial seal strength.
The proposed exterior material achieves high levels of both seal strength and initial seal strength at elevated temperatures, effectively addressing the heat resistance limitations of existing materials.
Smart Images

Figure 0007665920000003 
Figure 0007665920000004 
Figure 0007665920000005
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an exterior material for an electricity storage device, a manufacturing method thereof, and a method for selecting a sealant film to be used as a sealant layer in an exterior material for an electricity storage device. [Background technology]
[0002] Known examples of power storage devices include secondary batteries such as lithium ion batteries, nickel metal hydride batteries, and lead storage batteries, as well as electrochemical capacitors such as electric double layer capacitors. Due to the miniaturization of portable devices or the limitations of installation space, there is a demand for further miniaturization of power storage devices, and lithium ion batteries with high energy density have attracted attention. Metal cans have traditionally been used as exterior materials for lithium ion batteries, but multilayer films that are lightweight, have high heat dissipation properties, and can be produced at low cost have come to be used.
[0003] A lithium ion battery using the above multilayer film as an exterior material is called a laminated lithium ion battery. The exterior material covers the battery contents (positive electrode, separator, negative electrode, electrolyte, etc.) and prevents moisture from penetrating into the battery. A laminated lithium ion battery is manufactured, for example, by forming a recess in a part of the exterior material by cold forming, accommodating the battery contents in the recess, folding back the remaining part of the exterior material, and heat sealing the edges (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-101765 A Summary of the Invention [Problem to be solved by the invention]
[0005] Meanwhile, research and development is being conducted on a power storage device called an all-solid-state battery as a next-generation battery of lithium-ion batteries. An all-solid-state battery is characterized by using a solid electrolyte as the electrolyte, rather than an organic electrolyte. While a lithium-ion battery cannot be used at temperatures higher than the boiling point of the electrolyte (about 80°C), an all-solid-state battery can be used at temperatures exceeding 100°C, and the conductivity of lithium ions can be increased by operating it under high temperature conditions (for example, 100 to 150°C).
[0006] However, when using such a laminated body as an exterior material to manufacture a laminate-type all-solid-state battery, there is a risk that the heat resistance of the exterior material will be insufficient, resulting in insufficient sealing of the package of the all-solid-state battery.
[0007] The present disclosure provides an exterior material for an electricity storage device that can achieve sufficiently high levels of both seal strength at high temperatures and initial seal strength, and a method for producing the same. The present disclosure also provides a method for selecting a sealant film to be used as a sealant layer in the exterior material for an electricity storage device. [Means for solving the problem]
[0008] An exterior material for an energy storage device according to one aspect of the present disclosure has a laminated structure including at least a base material layer, a barrier layer, and a sealant layer, in this order, and the sealant layer has at least one minor dispersion peak γ in the range of −130°C to −50°C in a profile of loss tangent tanδ obtained by dynamic viscoelasticity measurement under a condition of 1.0 Hz.
[0009] The sub-dispersion peak γ is an index of molecular motion of the resin material constituting the sealant layer, specifically, a parameter reflecting the local twisting motion of the main chain in the crystalline and amorphous parts of the resin material and the thermal motion of the entire side chain. According to the study by the inventors, a sealant layer that satisfies the above requirements for the sub-dispersion peak γ contains a resin material that starts molecular motion at a relatively high temperature, and can exhibit excellent sealing strength at high temperatures. Note that the lower the temperature at which the sub-dispersion peak γ appears, the more flexible the sealant layer is, and the higher the temperature at which the sub-dispersion peak γ appears, the more heat-resistant the sealant layer is.
[0010] The sealant layer preferably has at least one main dispersion peak α in the range of 30°C to 130°C of the tan δ profile. The main dispersion peak α is a parameter that reflects the micro-Brownian motion of molecular chains of the amorphous part in the vicinity of the glass transition temperature (Tg) of the resin material contained in the sealant layer. According to the study by the present inventors, a sealant layer that satisfies the above requirements regarding the main dispersion peak α contains a resin material that starts molecular motion at a relatively low temperature (for example, room temperature) and is excellent in flexibility. Therefore, the sealant layer can exhibit even better sealing strength (initial sealing strength) in a room temperature environment. Note that the lower the temperature at which the main dispersion peak α appears, the more flexible the sealant layer is, and the higher the temperature at which the main dispersion peak α appears, the more heat-resistant the sealant layer is.
[0011] The sealant layer preferably contains a plasticizer. The temperature at which the minor dispersion peak γ and the major dispersion peak α appear can be controlled by adjusting the content of the plasticizer in the sealant layer. For example, the minor dispersion peak γ and the major dispersion peak α can be shifted to a lower temperature side by increasing the content of the plasticizer.
[0012] The sealant layer preferably contains a hydrogen sulfide adsorption material. In the all-solid-state battery, for example, a sulfide-based electrolyte, an oxide-based electrolyte, or an organic polymer electrolyte is used as the electrolyte. When a sulfide-based electrolyte is used, hydrogen sulfide is generated when moisture is mixed into the cell, and there is a concern that the adhesive strength between the barrier layer (e.g., metal foil) and the sealant layer may decrease. When the sealant layer contains a hydrogen sulfide adsorption material, it is possible to maintain excellent seal strength at room temperature and high temperatures even after exposure to hydrogen sulfide. The above-mentioned exterior material for a storage battery device may further include an adhesive layer provided between the barrier layer and the sealant layer, and in this case, the adhesive layer may contain a hydrogen sulfide adsorption material. From the viewpoint of the content of the hydrogen sulfide adsorption material, it is preferable that at least the sealant layer contains a hydrogen sulfide adsorption material.
[0013] The electrical storage device packaging material preferably further comprises a corrosion prevention treatment layer provided on at least one surface of the barrier layer. By providing the electrical storage device packaging material with the acid-resistant corrosion prevention treatment layer, excellent seal strength can be maintained at room temperature and at high temperatures even after exposure to hydrogen sulfide, and improved seal strength can be confirmed even before exposure to hydrogen sulfide.
[0014] One aspect of the present disclosure relates to a method for selecting a sealant film to be used as a sealant layer in an exterior material for an electricity storage device, the selection method including the following steps. (A) A process of performing dynamic viscoelasticity measurement on the sealant film to be evaluated at 1.0 Hz (B) A step of determining whether or not at least one sub-dispersion peak γ exists in the range of −130° C. to −50° C. in the profile of tan δ obtained by the dynamic viscoelasticity measurement.
[0015] By using a sealant film in which at least one secondary dispersion peak γ exists in the range of -130°C to -50°C in the above-mentioned tan δ profile for the sealant layer, it is possible to produce an exterior material for a storage battery device having sufficiently high levels of both seal strength at high temperatures and initial seal strength.
[0016] A manufacturing method for an exterior material for a storage battery device according to one aspect of the present disclosure includes the steps of preparing a sealant film determined in the above-mentioned selection method to have at least one minor dispersion peak γ in the range of −130°C to −50°C in the tan δ profile, and bonding the sealant film to a barrier layer. Effect of the Invention
[0017] According to the present disclosure, there is provided an exterior material for an electrical storage device that can achieve sufficiently high levels of both seal strength at high temperatures and initial seal strength, and a method for producing the same. Also, according to the present disclosure, there is provided a method for selecting a sealant film to be used as a sealant layer in the exterior material for an electrical storage device. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a perspective view showing an example of an all-solid-state battery including an exterior material according to the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view that illustrates an embodiment of the exterior material. [Diagram 3] 3(a) to 3(c) are cross-sectional views that typically show the configuration of the sealant layer. [Figure 4] FIG. 4 is a cross-sectional view taken along line IV-IV in FIG. 1, and is a diagram illustrating a schematic configuration of a tab (a resin film for terminal and a metal terminal) of the all-solid-state battery. [Diagram 5] FIG. 2 is a plan view diagrammatically illustrating an evaluation sample prepared in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, an embodiment of the present disclosure will be described in detail with reference to the drawings. In the drawings, the same or corresponding parts are denoted by the same reference numerals, and duplicated explanations will be omitted. In addition, the dimensional ratios of the drawings are not limited to the illustrated ratios.
[0020] <Electricity storage device> Fig. 1 is a perspective view showing a schematic configuration of a power storage device according to the present embodiment. In Fig. 1, an all-solid-state battery is illustrated as an example of a power storage device 100, and the following description will be given. Note that the power storage device having the configuration shown in Fig. 1 may be called a battery pack or a battery cell.
[0021] The energy storage device 100 is an all-solid-state battery, and includes an energy storage device body 50, an exterior material 10, a pair of metal terminals 30, and a terminal resin film 40 (tab sealant). The energy storage device body 50 is a battery body that performs charging and discharging. The exterior material 10 covers the surface of the energy storage device body 50, and is disposed so as to be in contact with a part of the terminal resin film 40.
[0022] [Exterior material] 2 is a cross-sectional view showing an example of a cut surface of the exterior material 10. The exterior material 10 has a multilayer structure including, from the outside to the inside (the electricity storage device main body 50 side), a base material layer 11, a first adhesive layer 12, a barrier layer 13, a corrosion prevention treatment layer 14, a second adhesive layer 17, and a sealant layer 16, in this order.
[0023] (Sealant layer) The sealant layer 16 has at least one sub-dispersion peak γ in the range of −130° C. to −50° C. in the profile of the loss tangent tanδ obtained by dynamic viscoelasticity measurement under the condition of 1.0 Hz. When the sealant layer 16 satisfies this condition, the exterior material 10 can achieve both the seal strength at high temperatures and the initial seal strength (seal strength at room temperature) at a sufficiently high level. The temperature range in which the sub-dispersion peak γ exists is preferably −120° C. to −60° C., more preferably −110° C. to −70° C., from the viewpoint of the seal strength at room temperature and at high temperatures. If the temperature in which the sub-dispersion peak γ exists is less than −130° C., the heat resistance of the sealant layer 16 may be poor, and the seal strength at high temperatures may be insufficient. On the other hand, if the temperature in which the sub-dispersion peak γ exists exceeds −50° C., the flexibility of the sealant layer 16 may be poor, and the seal strength at room temperature may be insufficient.
[0024] The above-mentioned tan δ can be calculated as the loss tangent tan δ from the loss modulus E″ and the storage modulus E′, for example, by immersing the exterior material in an aqueous sodium hydroxide solution to dissolve the barrier layer (metal foil) and extracting a film consisting of only the sealant layer, and measuring the extracted film under the following conditions using a dynamic viscoelasticity device (manufactured by SII, product name: DMS6100) in accordance with a method in accordance with JIS K7244-4. Peeling mode: Pulling Heating rate: 2℃ / min Temperature range: -150~150℃ Frequency: 1.0Hz
[0025] The sealant layer 16 preferably has at least one main dispersion peak α in the range of 30°C to 130°C of the above tan δ profile. When the sealant layer 16 satisfies this condition, the exterior material 10 exhibits even better initial seal strength (seal strength at room temperature). The temperature range in which the main dispersion peak α exists is preferably 40°C to 110°C, more preferably 50°C to 100°C, from the viewpoint of seal strength at room temperature. If the temperature in which the main dispersion peak α exists is less than 30°C, the heat resistance of the sealant layer 16 tends to be poor and the seal strength at high temperatures tends to be insufficient. On the other hand, if the temperature in which the main dispersion peak α exists exceeds 130°C, the flexibility of the sealant layer 16 tends to be poor and the seal strength at room temperature tends to be insufficient.
[0026] The temperature at which the minor dispersion peak γ and the major dispersion peak α of the sealant layer 16 appear can be controlled, for example, by the structure of the base resin material contained in the sealant layer 16, the stretching ratio of the sealant layer 16, or the amount of additives (e.g., plasticizers) blended. The sealant layer 16 contains additives as necessary. Examples of additives include plasticizers, antioxidants, slip agents, flame retardants, AB agents, light stabilizers, dehydrating agents, and tackifiers.
[0027] Examples of the base resin material contained in the sealant layer 16 include polyester-based, polyolefin-based, and polyamide-based resins.
[0028] The polyester resin can be obtained by copolymerizing an acid component and a glycol component. Examples of the acid component include phthalic acid, terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, cyclohexanedicarboxylic acid, adipic acid, and sebacic acid. Examples of the glycol component include ethylene glycol, butanediol, pentanediol, hexanediol, neopentyl glycol, diethylene glycol, polytetramethylene glycol, cyclohexanedimethanol, and propanediol. According to the study by the present inventors, the temperature at which the secondary dispersion peak γ exists in the general PET (copolymer of terephthalic acid and ethylene glycol) is outside the range of −130° C. to −50° C., and the seal strength at room temperature is insufficient. When a plasticizer is not blended in the sealant layer 16, it is preferable that the sealant layer 16 contains a polyester resin in which one acid component and two or more glycol components are copolymerized.
[0029] Examples of polyolefin resins include polyethylene and polypropylene resins. Since commonly used polyolefin resins have poor heat resistance, it is preferable to use polyethylene or polypropylene modified with amide or the like. When the sealant layer 16 and the barrier layer 13 are bonded together by thermal lamination, it is preferable to use polyolefin modified with an acid such as carboxylic acid or maleic anhydride, or modified with amide, from the viewpoint of metal adhesion.
[0030] Examples of polyamide resins include nylon 6 and nylon 6,6.
[0031] From the viewpoint of adjusting the temperature at which the minor dispersion peak γ and the major dispersion peak α of the sealant layer 16 appear, the sealant layer 16 preferably contains a plasticizer. As the plasticizer, for example, an ester-based compound can be used. Specific examples include glycol diesters, adipic acid esters, phthalic acid esters, diacetyl monoacyl glycerol derivatives, and esters having an ether skeleton. Although it depends on the base resin material of the sealant layer 16, the content of the plasticizer in the sealant layer 16 is preferably 30 mass% or less based on the mass of the sealant layer 16. When an excessive amount of plasticizer is blended in the sealant layer 16, the temperature at which the minor dispersion peak γ and the major dispersion peak α appear is excessively lowered, and the cohesive force tends to decrease.
[0032] The sealant layer 16 may have a single layer structure or a multi-layer structure of two or more layers (see Figs. 3(a) to 3(c)). When the sealant layer has a single layer structure, its thickness is preferably 10 to 300 µm, and more preferably 20 to 100 µm. When the thickness of the sealant layer 16 is 10 µm or more, it is easy to ensure sealing properties and insulation properties, while when the thickness is 300 µm or less, it is possible to ensure the cell volume.
[0033] FIG. 3(b) is a cross-sectional view that shows a two-layer structure of the sealant layer 16. The sealant layer 16 shown in the figure has a first resin layer 16a and a second resin layer 16b formed on the inner surface of the first resin layer 16a. The first resin layer 16a may be made of a different material from the second resin layer 16b, for example, and may have a different thickness from the second resin layer 16b. The thicknesses of the first resin layer 16a and the second resin layer 16b are, for example, 5 to 300 μm, and may be 20 to 200 μm. As shown in FIG. 3(c), the sealant layer 16 may have a three-layer structure and further include a third resin layer 16c.
[0034] When the electrolyte of the all-solid-state battery is a sulfide-based electrolyte, the sealant layer 16 preferably contains a hydrogen sulfide adsorbent. By containing the hydrogen sulfide adsorbent, the sealant layer 16 can maintain excellent seal strength at room temperature and at high temperatures even after exposure to hydrogen sulfide. As the hydrogen sulfide adsorbent, a material having the ability to absorb or adsorb hydrogen sulfide can be used. Specific examples thereof include zinc oxide, amorphous metal silicate, hydroxide of zirconium and lanthanoid elements, tetravalent metal phosphate, potassium permanganate, sodium permanganate, aluminum oxide, iron hydroxide, silver sulfate, silver acetate, isocyanate compounds, aluminum silicate, potassium aluminum sulfate, zeolite, activated carbon, amine compounds, and ionomers.
[0035] The content of the hydrogen sulfide adsorption substance in the sealant layer 16 is preferably 1 to 50 mass %, more preferably 2 to 25 mass %, and even more preferably 5 to 15 mass %, based on the mass of the sealant layer 16. When the content of the hydrogen sulfide adsorption substance in the sealant layer 16 is 1 mass % or more, the hydrogen sulfide adsorption effect is exhibited, while when the content is 50 mass % or less, the sealant layer 16 can achieve both adhesion and sealant suitability. When the sealant layer 16 has a multi-layer structure, all or a part of the layers may contain the hydrogen sulfide adsorption substance. Note that a layer other than the sealant layer 16 (for example, the second adhesive layer 17) in the exterior packaging material 10 may contain a sulfide-based electrolyte, but from the viewpoint of the content of the hydrogen sulfide adsorption substance, it is preferable that at least the sealant layer 16 contains the hydrogen sulfide adsorption substance.
[0036] (base material layer) The base layer 11 provides heat resistance in the sealing process when manufacturing the electricity storage device and plays a role in suppressing the occurrence of pinholes that may occur during molding and distribution. In particular, in the case of an exterior material for a large-scale electricity storage device, the base layer 11 can also provide scratch resistance, chemical resistance, insulation, and the like.
[0037] The base layer 11 is preferably a layer formed of an insulating resin, such as polyester resin, polyamide resin, polyimide resin, polyamideimide resin, polyetherketone resin, polyphenylene sulfide resin, polyetherimide resin, polysulfone resin, fluororesin, phenol resin, melamine resin, urethane resin, allyl resin, silicone resin, epoxy resin, furan resin, acetyl cellulose resin, or the like.
[0038] When these resins are applied to the substrate layer, they may be in the form of a stretched or unstretched film, or in the form of a coating film. The substrate layer may be a single layer or a multilayer, and in the case of a multilayer, different resins may be used in combination. In the case of a film, a co-extruded film or a film laminated with an adhesive may be used. In the case of a coating film, a film coated with the number of layers may be used, and a multilayer film may be formed by combining a film and a coating film.
[0039] Among these resins, polyester resin and polyamide resin are preferable for the base layer because of their excellent moldability. Examples of polyester resin include polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. Examples of polyamide resin constituting the polyamide film include nylon 6, nylon 6,6, a copolymer of nylon 6 and nylon 6,6, nylon 6, nylon 9T, nylon 10, polymetaxylylene adipamide (MXD6), nylon 11, and nylon 12.
[0040] When these resins are used in the form of a film, it is preferably a biaxially stretched film. Examples of the stretching method for the biaxially stretched film include sequential biaxial stretching, tubular biaxial stretching, and simultaneous biaxial stretching. From the viewpoint of obtaining better deep drawing formability, the biaxially stretched film is preferably one stretched by the tubular biaxial stretching method.
[0041] The thickness of the substrate layer 11 is preferably 6 to 40 μm, and more preferably 10 to 30 μm. When the thickness of the substrate layer 11 is 6 μm or more, the pinhole resistance and insulating properties of the packaging material 10 tend to be improved. When the thickness of the substrate layer 11 exceeds 40 μm, the total thickness of the packaging material 10 tends to be large.
[0042] In order to suppress deformation of the substrate during sealing, the peak melting temperature of the substrate layer is higher than the peak melting temperature of the sealant layer, and is preferably 30° C. or higher.
[0043] (First adhesive layer) The first adhesive layer 12 is a layer that bonds the base layer 11 and the barrier layer 13. Specific examples of materials constituting the first adhesive layer 12 include polyurethane resins in which a bifunctional or higher isocyanate compound is reacted with a base material such as polyester polyol, polyether polyol, acrylic polyol, or carbonate polyol. The above-mentioned various polyols can be used alone or in combination of two or more types depending on the functions and performance required for the exterior material. In addition, the above-mentioned polyurethane resins may be mixed with various other additives and stabilizers depending on the performance required for the adhesive.
[0044] The thickness of the first adhesive layer 12 is not particularly limited, but from the viewpoint of obtaining desired adhesive strength, conformability, processability, and the like, the thickness is, for example, preferably 1 to 10 μm, and more preferably 3 to 7 μm.
[0045] (Barrier layer) The barrier layer 13 has water vapor barrier properties that prevent moisture from penetrating into the inside of the electricity storage device. The barrier layer 13 also has extensibility for deep drawing. As the barrier layer 13, various metal foils such as aluminum, stainless steel, and copper, metal vapor deposition films, inorganic oxide vapor deposition films, carbon-containing inorganic oxide vapor deposition films, films provided with these vapor deposition films, and the like can be used. In terms of mass (specific gravity), moisture resistance, processability, and cost, metal foils are preferred, and aluminum foil is more preferred.
[0046] As the aluminum foil, a soft aluminum foil that has been annealed can be preferably used from the viewpoint of imparting desired ductility during molding, but it is more preferable to use an aluminum foil containing iron for the purpose of imparting further pinhole resistance and ductility during molding. The content of iron in the aluminum foil is preferably 0.1 to 9.0 mass%, more preferably 0.5 to 2.0 mass%, in 100 mass% of the aluminum foil. When the iron content is 0.1 mass% or more, an exterior material 10 having better pinhole resistance and ductility can be obtained. When the iron content is 9.0 mass% or less, an exterior material 10 having better flexibility can be obtained. Although untreated aluminum foil may be used, it is preferable to use an aluminum foil that has been degreased in terms of imparting corrosion resistance. When the aluminum foil is degreased, the degreased treatment may be performed on only one side of the aluminum foil, or on both sides.
[0047] The thickness of the barrier layer 13 is not particularly limited, but taking into consideration the barrier properties, pinhole resistance, and processability, it is preferably 9 to 200 μm, and more preferably 15 to 100 μm.
[0048] (Corrosion prevention treatment layer) The corrosion prevention treatment layer 14 is a layer provided on the surface of the barrier layer 13 to prevent corrosion of the thin metal layer or the like that constitutes the barrier layer 13. The corrosion prevention treatment layer 14 is formed, for example, by degreasing treatment, hydrothermal conversion treatment, anodizing treatment, chemical conversion treatment, or a combination of these treatments.
[0049] The degreasing treatment may be acid degreasing or alkaline degreasing. The acid degreasing may be a method using an inorganic acid such as sulfuric acid, nitric acid, hydrochloric acid, or hydrofluoric acid alone or a mixture thereof. In addition, by using an acid degreasing agent obtained by dissolving a fluorine-containing compound such as monosodium ammonium difluoride in the inorganic acid as the acid degreasing, not only can the aluminum be degreased, but also a passive aluminum fluoride can be formed, which is effective in terms of hydrofluoric acid resistance, particularly when an aluminum foil is used for the barrier layer 13. The alkaline degreasing may be a method using sodium hydroxide or the like.
[0050] An example of the hydrothermal modification treatment is boehmite treatment in which an aluminum foil is immersed in boiling water containing triethanolamine. An example of the anodization treatment is alumite treatment.
[0051] The chemical conversion treatment may be of the immersion type or the coating type. Examples of the immersion type chemical conversion treatment include chromate treatment, zirconium treatment, titanium treatment, vanadium treatment, molybdenum treatment, calcium phosphate treatment, strontium hydroxide treatment, cerium treatment, ruthenium treatment, and various chemical conversion treatments consisting of a mixture of these. On the other hand, examples of the coating type chemical conversion treatment include a method in which a coating agent having corrosion prevention properties is applied onto the barrier layer 13.
[0052] When forming at least a part of the corrosion prevention layer by any of these corrosion prevention treatments, namely hydrothermal conversion treatment, anodizing treatment, and chemical conversion treatment, it is preferable to perform the above-mentioned degreasing treatment in advance. Note that, when using a degreased metal foil, such as a metal foil that has been subjected to an annealing process, as the barrier layer 13, there is no need to perform a degreasing treatment again in forming the corrosion prevention layer 14.
[0053] The coating agent used in the spray-type chemical conversion treatment preferably contains trivalent chromium. The coating agent may also contain at least one polymer selected from the group consisting of cationic polymers and anionic polymers, which will be described later.
[0054] Among the above treatments, particularly in hydrothermal conversion treatment and anodization treatment, the aluminum foil surface is dissolved by a treatment agent to form an aluminum compound (boehmite, alumite) with excellent corrosion resistance. Therefore, since a bicontinuous structure is formed from the barrier layer 13 using the aluminum foil to the corrosion prevention treatment layer 14, the above treatment is included in the definition of chemical conversion treatment. On the other hand, as described later, it is also possible to form the corrosion prevention treatment layer 14 by a pure coating method alone, which is not included in the definition of chemical conversion treatment. As an example of this method, a method using a sol of a rare earth element oxide such as cerium oxide with an average particle size of 100 nm or less can be mentioned, which has an aluminum corrosion prevention effect (inhibitor effect) and is also environmentally friendly. By using this method, it is possible to impart a corrosion prevention effect to metal foil such as aluminum foil even with a general coating method.
[0055] Examples of the rare earth oxide sol include sols using various solvents such as water-based, alcohol-based, hydrocarbon-based, ketone-based, ester-based, and ether-based solvents. Among these, water-based sols are preferred. In order to stabilize the dispersion of the rare earth oxide sol, inorganic acids such as nitric acid, hydrochloric acid, and phosphoric acid or their salts, and organic acids such as acetic acid, malic acid, ascorbic acid, and lactic acid are usually used as dispersion stabilizers. Among these dispersion stabilizers, phosphoric acid is particularly expected to (1) stabilize the dispersion of the sol, (2) improve adhesion to the barrier layer 13 by utilizing the aluminum chelating ability of phosphoric acid, and (3) improve the cohesive force of the corrosion prevention treatment layer 14 (oxide layer) by easily causing dehydration condensation of phosphoric acid even at low temperatures.
[0056] The corrosion prevention treatment layer 14 formed by the rare earth element oxide sol is an aggregate of inorganic particles, and therefore the layer itself may lose its cohesive strength even after the dry curing process. Therefore, in this case, the corrosion prevention treatment layer is preferably compounded with the following anionic polymer or cationic polymer to supplement the cohesive strength.
[0057] The corrosion prevention treatment layer is not limited to the above-mentioned layers. For example, it may be formed using a treatment agent in which phosphoric acid and a chromium compound are mixed with a resin binder (such as aminophenol), as in the case of coating-type chromate, which is a known technology. By using this treatment agent, a layer having both corrosion prevention function and adhesion can be obtained. In addition, although it is necessary to consider the stability of the coating liquid, a coating agent in which a rare earth element oxide sol and a polycationic polymer or a polyanionic polymer are previously mixed into a one-component solution can be used to obtain a layer having both corrosion prevention function and adhesion.
[0058] The mass per unit area of the corrosion prevention treatment layer is 0.005 to 0.200 g / m2, whether it is a multi-layer structure or a single-layer structure. 2 is preferable, and 0.010 to 0.100 g / m 2 It is more preferable that the mass per unit area is 0.005 g / m 2 If the mass per unit area is 0.200 g / m or more, it is easy to impart a corrosion prevention function to the barrier layer 13. 2 Even if the thickness exceeds 100 mm, the corrosion prevention function does not change much. On the other hand, when a rare earth oxide sol is used, if the coating is thick, the heat curing during drying may be insufficient, which may result in a decrease in cohesive force. The thickness of the corrosion prevention treatment layer 14 can be calculated from its specific gravity.
[0059] From the viewpoint of adhesion between the sealant layer and the barrier layer, the corrosion prevention treatment layer may be, for example, an embodiment that contains cerium oxide, 1 to 100 parts by mass of phosphoric acid or a phosphate relative to 100 parts by mass of the cerium oxide, and a cationic polymer, or an embodiment that is formed by subjecting the barrier layer 13 to a chemical conversion treatment, or an embodiment that is formed by subjecting the barrier layer to a chemical conversion treatment and contains a cationic polymer.
[0060] (Second adhesive layer) The second adhesive layer 17 is a layer that bonds the barrier layer 13, on which the corrosion prevention treatment layer 14 is formed, to the sealant layer 16. For the second adhesive layer 17, a general adhesive for bonding the barrier layer 13 and the sealant layer 16 can be used.
[0061] When the corrosion prevention treatment layer 14 has a layer containing at least one type of polymer selected from the group consisting of the above-mentioned cationic polymers and anionic polymers, the second adhesive layer 17 is preferably a layer containing a compound (hereinafter also referred to as a "reactive compound") that is reactive with the above-mentioned polymer contained in the corrosion prevention treatment layer 14.
[0062] For example, when the corrosion prevention treatment layer 14 contains a cationic polymer, the second adhesive layer 17 contains a compound reactive with the cationic polymer. When the corrosion prevention treatment layer 14 contains an anionic polymer, the second adhesive layer 17 contains a compound reactive with the anionic polymer. When the corrosion prevention treatment layer 14 contains a cationic polymer and an anionic polymer, the second adhesive layer 17 contains a compound reactive with the cationic polymer and a compound reactive with the anionic polymer. However, the second adhesive layer 17 does not necessarily have to contain the above two types of compounds, and may contain a compound reactive with both the cationic polymer and the anionic polymer. Here, "reactive" means to form a covalent bond with the cationic polymer or the anionic polymer. The second adhesive layer 17 may further contain an acid-modified polyolefin resin.
[0063] The compound reactive with the cationic polymer may be at least one compound selected from the group consisting of a polyfunctional isocyanate compound, a glycidyl compound, a compound having a carboxy group, and a compound having an oxazoline group.
[0064] Examples of the polyfunctional isocyanate compound, glycidyl compound, compound having a carboxy group, and compound having an oxazoline group include the polyfunctional isocyanate compound, glycidyl compound, compound having a carboxy group, and compound having an oxazoline group, which are exemplified above as crosslinking agents for forming a crosslinked structure from a cationic polymer. Among these, the polyfunctional isocyanate compound is preferred in terms of high reactivity with the cationic polymer and ease of forming a crosslinked structure.
[0065] The compound reactive with anionic polymers includes at least one compound selected from the group consisting of glycidyl compounds and compounds having oxazoline groups.These glycidyl compounds and compounds having oxazoline groups include the glycidyl compounds and compounds having oxazoline groups exemplified above as crosslinking agents for forming cationic polymers into crosslinked structures.Among these, glycidyl compounds are preferred because of their high reactivity with anionic polymers.
[0066] When the second adhesive layer 17 contains an acid-modified polyolefin resin, it is preferable that the reactive compound also has a reactivity with the acidic group in the acid-modified polyolefin resin (i.e., forms a covalent bond with the acidic group). This further enhances the adhesion to the corrosion prevention treatment layer 14. In addition, the acid-modified polyolefin resin has a crosslinked structure, further improving the solvent resistance of the exterior material 10.
[0067] The content of the reactive compound is preferably from an equivalent amount to 10 times the equivalent amount of the acidic group in the acid-modified polyolefin resin. If it is an equivalent amount or more, the reactive compound reacts sufficiently with the acidic group in the acid-modified polyolefin resin. On the other hand, if it exceeds 10 times the equivalent amount, the crosslinking reaction with the acid-modified polyolefin resin is sufficiently saturated, so that there is a concern of the presence of unreacted substances and a decrease in various performances. Therefore, for example, the content of the reactive compound is preferably 5 to 20 parts by mass (solid content ratio) per 100 parts by mass of the acid-modified polyolefin resin.
[0068] The acid-modified polyolefin resin is a polyolefin resin to which an acidic group has been introduced. Examples of the acidic group include a carboxyl group, a sulfonic acid group, and an acid anhydride group, and maleic anhydride groups and (meth)acrylic acid groups are particularly preferred. For example, the acid-modified polyolefin resin may be the same as the modified polyolefin resin used in the sealant layer 16.
[0069] The second adhesive layer 17 may contain various additives such as a flame retardant, a slip agent, an antiblocking agent, an antioxidant, a light stabilizer, and a tackifier.
[0070] Examples of adhesives that form the second adhesive layer 17 include polyurethane resins in which a difunctional or higher isocyanate compound is reacted with a base material such as polyester polyol, polyether polyol, acrylic polyol, or carbonate polyol, and epoxy resins in which an amine compound or the like is reacted with a base material having an epoxy group, and these are preferred from the standpoint of heat resistance.
[0071] The thickness of the second adhesive layer 17 is not particularly limited, but from the viewpoint of obtaining the desired adhesive strength, processability, and the like, it is preferably 1 to 10 μm, and more preferably 2 to 7 μm.
[0072] [Metal terminal] Fig. 4 is a cross-sectional view of the terminal resin film and the metal terminal shown in Fig. 1 in the direction of line IV-IV. Of the pair of metal terminals 30, 30, one metal terminal 30 is electrically connected to the positive electrode of the electricity storage device main body 50, and the other metal terminal 30 is electrically connected to the negative electrode of the electricity storage device main body 50. The pair of metal terminals 30, 30 extend from the electricity storage device main body 50 to the outside of the exterior material 10. The shape of the pair of metal terminals 30, 30 may be, for example, a flat plate shape.
[0073] Metals can be used as the material of the metal terminal 30. The metal to be used as the material of the metal terminal 30 may be determined in consideration of the structure of the power storage device main body 50 and the materials of its components. For example, when the power storage device 100 is an all-solid-state battery, aluminum is preferably used as the material of the metal terminal 30 connected to the positive electrode of the power storage device main body 50. Copper having a nickel plating layer formed on the surface, or nickel, is preferably used as the material of the metal terminal 30 connected to the negative electrode of the power storage device main body 50.
[0074] The thickness of the metal terminal 30 depends on the size and capacity of the all-solid-state battery. In the case of a small all-solid-state battery, the thickness of the metal terminal 30 may be, for example, 50 μm or more. In the case of a large all-solid-state battery for power storage, vehicle mounting, etc., the thickness of the metal terminal 30 may be appropriately set within the range of, for example, 100 to 500 μm.
[0075] [Resin film for terminals] As shown in Fig. 4, the terminal resin film 40 is disposed so as to cover a portion of the outer circumferential surface of the metal terminal 30. By disposing the terminal resin film 40 between the metal terminal 30 and the exterior material 10, the sealing and insulating properties of the electricity storage device 100 can be achieved at an even higher level. The terminal resin film 40 has heat resistance equal to or greater than that of the above-mentioned sealant layer 16 and base material layer 11. Note that, if the sealant layer 16 of the exterior material 10 can sufficiently ensure the sealing and insulating properties of the electricity storage device 100, the terminal resin film 40 does not need to be used.
[0076] Although the embodiment of the present disclosure has been described above in detail, the present invention is not limited to the above embodiment, and various modifications and changes are possible within the scope of the gist of the present disclosure described in the claims. For example, in the above embodiment, the corrosion prevention treatment layer 14 is provided only on one surface (the second adhesive layer 17 side) of the barrier layer 13, but the corrosion prevention treatment layer 14 may also be provided on the other surface (the first adhesive layer 12 side) of the barrier layer 13. In addition, for example, when the sealant layer 16 is attached to the barrier layer 13 by thermal lamination, the second adhesive layer 17 may not be provided. When the base layer 11 is provided by coating or painting, the first adhesive layer 12 may not be provided. In the above embodiment, an electric solid battery is exemplified as an electric storage device to which the exterior material 10 is applied, but the exterior material 10 may be applied to other electric storage devices (for example, lithium ion batteries).
[0077] A method for selecting a sealant film may be carried out based on the contents of the above embodiment. That is, this selection method is for selecting a sealant film to be used as a sealant layer in an exterior material for a storage battery device, and may include (A) a step of performing dynamic viscoelasticity measurement on the sealant film to be evaluated under a condition of 1.0 Hz, and (B) a step of judging whether or not at least one sub-dispersion peak γ exists in the range of −130° C. to −50° C. in the profile of tan δ obtained by the dynamic viscoelasticity measurement. The matters described in the above embodiment may be appropriately applied to this selection method. EXAMPLES
[0078] The present disclosure will be described more specifically below based on examples, but the present disclosure is not limited to the following examples.
[0079] [Materials used] The materials used in the examples and comparative examples are shown below.
[0080] <Base layer (thickness 25 μm)> A polyethylene terephthalate film (thickness: 25 μm) was prepared as a substrate layer, and one surface of the film was subjected to a corona treatment.
[0081] <First adhesive layer (thickness 4 μm)> A polyurethane adhesive (manufactured by Toyo Ink Co., Ltd.) was used, which is a mixture of a polyester polyol-based base material and a tolylene diisocyanate adduct-based curing agent.
[0082] <First corrosion prevention treatment layer (base layer side) and second corrosion prevention treatment layer (sealant layer side)> (CL-1): A 1% by mass phosphoric acid aqueous solution was used as the solvent. The solid content of water-soluble phenolic resin (manufactured by Sumitomo Bakelite Co., Ltd.) was adjusted to 1% by mass. Chromium fluoride (CrF3) was added to the water-soluble phenolic resin (manufactured by Sumitomo Bakelite Co., Ltd.) at a concentration of 10 mg / m2 as the amount of Cr present in the final dried film. 2 The chemical conversion treatment agent was used with its concentration adjusted so as to satisfy the following criteria: (CL-2): "Sodium polyphosphate stabilized cerium oxide sol" was used, which was adjusted to a solid content concentration of 10% by mass using distilled water as a solvent. The sodium polyphosphate stabilized cerium oxide sol was obtained by mixing 100 parts by mass of cerium oxide with 10 parts by mass of sodium salt of phosphoric acid. (CL-3): A composition consisting of 90% by mass of "polyallylamine (manufactured by Nitto Boseki Co., Ltd.)" adjusted to a solid content concentration of 5% by mass using distilled water as a solvent, and 10% by mass of "polyglycerol polyglycidyl ether (manufactured by Nagase ChemteX Corporation)" was used.
[0083] <Barrier layer (thickness 40 μm)> Annealed and degreased soft aluminum foil (manufactured by Toyo Aluminum Co., Ltd., "Material 8079") was used.
[0084] <Second adhesive layer> An epoxy adhesive (ADEKA EP4100 / EH4602 = 100 / 25 (mass ratio)) was diluted with ethyl acetate to a solid content of 30% and used. The coating amount after drying was 3 g / m 2 The sealant film was applied to the surface of the barrier layer (soft aluminum foil) so that the thickness of the sealant film was 100 μm. After drying at 80° C. for 1 minute, the barrier layer and the sealant film were laminated. Then, the sealant film was aged at 120° C. for 3 hours.
[0085] <Sealant layer> To form the sealant layer, the following materials were prepared. [Base resin] Polyester resin 1: A copolymer of terephthalic acid as the acid component and ethylene glycol as the glycol component. Polyester resin 2: A copolymer of terephthalic acid as the acid component and ethylene glycol and butanediol as the glycol component. Polyester resin 3: A copolymer of terephthalic acid and isophthalic acid as the acid component and ethylene glycol, butanediol and neopentyl glycol as the glycol component. Polyester resin 4: A copolymer of terephthalic acid as the acid component and ethylene glycol and 1,4-cyclohexanedimethanol as the glycol component. Polyester resin 5: A copolymer of terephthalic acid and isophthalic acid as the acid component and butanediol and hexanediol as the glycol component. Polyester resin 6: A copolymer of terephthalic acid and isophthalic acid as the acid component and butanediol and hexanediol as the glycol component (the proportion of butanediol is increased more than that of polyester resin 5) Polyester resin 7: A copolymer of naphthalenedicarboxylic acid as the acid component and 1,4-cyclohexanedimethanol as the glycol component. Polyester resin 8: A copolymer of terephthalic acid and isophthalic acid as the acid component and ethylene glycol and hexanediol as the glycol component. Polyolefin resin 1: Amide-modified polyethylene Polyolefin resin 2: Random polypropylene [Plasticizer] Glycol diester: 10 parts by weight per 100 parts by weight of the base resin material was mixed as required. [Hydrogen sulfide absorber] Zinc oxide: 3 parts by mass was mixed in with 100 parts by mass of the base resin material as required.
[0086] <Preparation of exterior materials> Example 1 First, a first and a second corrosion prevention treatment layer were provided on the barrier layer by the following procedure: (CL-1) was applied to both surfaces of the barrier layer in a dry coating amount of 30 mg / m 2 The coating was then applied by microgravure coating so that the coating became as shown in FIG. 1 and the coating was then baked at 200° C. in a drying unit (this treatment is referred to as “chemical conversion treatment”).
[0087] Next, the first corrosion prevention treatment layer side of the barrier layer was attached to the base layer using a polyurethane adhesive (first adhesive layer) by dry lamination. The second corrosion prevention treatment layer side of the barrier layer was attached to the sealant layer (thickness: 80 μm) using a polyurethane adhesive (second adhesive layer) by dry lamination. Through these steps, an exterior material according to Example 1 was obtained. The composition of the sealant layer was as follows. Polyester resin 1:100 parts by weight Plasticizer: 10 parts by weight Hydrogen sulfide adsorption material: 3 parts by weight
[0088] Example 2 Except for forming the first and second corrosion prevention treatment layers using (CL-2) and (CL-3) instead of (CL-1), an exterior material was produced in the same manner as in Example 1. That is, (CL-2) was applied to both surfaces of the barrier layer in a dry coating amount of 70 mg / m 2 The layer was then coated by microgravure coating so that the thickness of the layer was 200° C., and the layer was baked in a drying unit. Next, (CL-3) was applied on the layer obtained in a dry coating amount of 20 mg / m 2 By applying the coating by microgravure coating so that the above-mentioned coatings were formed, composite layers consisting of (CL-1) and (CL-2) were formed as the first and second corrosion prevention treatment layers (this treatment is called "composite treatment"). This composite layer exhibits corrosion prevention performance by combining the two types of coatings, (CL-2) and (CL-3).
[0089] Example 3 An exterior material was prepared in the same manner as in Example 2, except that a sealant layer was formed using a sealant material containing polyester-based resin 2 (plasticizer content: 10 parts by mass, hydrogen sulfide absorbent content: 3 parts by mass) instead of polyester-based resin 1.
[0090] Example 4 An exterior material was prepared in the same manner as in Example 2, except that no hydrogen sulfide absorbent was added to the sealant material.
[0091] Example 5 An exterior material was produced in the same manner as in Example 1, except that the barrier layer was not subjected to anticorrosive treatment, and no hydrogen sulfide absorbent was added to the sealant material.
[0092] Example 6 An exterior material was prepared in the same manner as in Example 1, except that no corrosion prevention treatment was applied to the barrier layer, and polyester-based resin 3 (plasticizer content: 0 parts by mass, hydrogen sulfide absorbent content: 0 parts by mass) was used as the sealant material.
[0093] Example 7 An exterior material was produced in the same manner as in Example 2, except that polyester resin 3 was used instead of polyester resin 1 and no plasticizer was added.
[0094] Example 8 An exterior material was produced in the same manner as in Example 7, except that Polyester-based resin 4 was used instead of Polyester-based resin 3.
[0095] Example 9 An exterior material was produced in the same manner as in Example 7, except that Polyester-based resin 5 was used instead of Polyester-based resin 3.
[0096] Example 10 An exterior material was produced in the same manner as in Example 7, except that Polyester-based resin 6 was used instead of Polyester-based resin 3.
[0097] Example 11 An exterior material was produced in the same manner as in Example 7, except that polyolefin resin 1 was used instead of polyester resin 3.
[0098] Example 12 Except for the fact that the barrier layer and the sealant layer were bonded together by the thermal lamination method instead of the dry lamination method, the exterior material was produced in the same manner as in Example 2. The thermal lamination method was carried out as follows. That is, a laminate of the base layer / first adhesive layer / first corrosion prevention treatment layer / barrier layer / second corrosion prevention treatment layer was set in the unwinding section of an extrusion laminator, and the material of the sealant layer was extruded onto the second corrosion prevention treatment layer under processing conditions of 270°C and 100m / min. The laminate thus obtained was wound around a roll heated to 220°C and transported, and the laminate was subjected to a heat treatment at 220°C for about 0.5 seconds to obtain an exterior material (base layer / first adhesive layer / first corrosion prevention treatment layer / barrier layer / second corrosion prevention treatment layer / sealant layer).
[0099] (Example 13) An exterior material was produced in the same manner as in Example 7, except that a sealant material containing both polyester-based resin 1 and polyester-based resin 7 was used instead of polyester-based resin 3. The composition of the sealant material was as follows. Polyester resin 1:50 parts by weight Polyester resin 7: 50 parts by weight Hydrogen sulfide adsorption material: 3 parts by weight
[0100] Comparative Example 1 An exterior material was produced in the same manner as in Example 7, except that a sealant material containing polyester-based resin 7 was used instead of polyester-based resin 3. The composition of the sealant material was as follows. Polyester resin 7: 100 parts by weight Hydrogen sulfide adsorption material: 3 parts by weight
[0101] Comparative Example 2 An exterior material was produced in the same manner as in Example 2, except that no plasticizer was added to the sealant material.
[0102] Comparative Example 3 An exterior material was produced in the same manner as in Example 7, except that Polyester-based resin 8 was used instead of Polyester-based resin 3.
[0103] Comparative Example 4 An exterior material was produced in the same manner as in Example 12, except that the polyolefin resin 2 was used instead of the polyester resin 1 and no hydrogen sulfide adsorbing substance was added.
[0104] <Evaluation> The exterior packaging materials obtained in the examples and comparative examples were subjected to the following evaluation tests.
[0105] [Loss tangent of sealant layer tanδ] The obtained exterior material was immersed in a sodium hydroxide solution to dissolve the barrier layer, and a film consisting of only the sealant layer was taken out. The film was then cut to a width of 10 mm (TD) and a length of 30 mm (MD) to prepare a measurement sample, and the chuck distance was held at 20 mm. Measurements were performed under the following conditions using a dynamic viscoelasticity device (manufactured by SII, product name: DMS6100) according to the method in accordance with JIS K7244-4, and the loss tangent tanδ was calculated from the loss modulus E'' and storage modulus E'. In addition, the temperature of the minor dispersion peak γ and the temperature of the major dispersion peak α were obtained from the obtained tanδ profile. The results are shown in Tables 1 and 2. Peeling mode: Pulling Heating rate: 2℃ / min Temperature range: -100~120℃ Frequency: 1.0Hz
[0106] [Initial seal strength] The exterior material was cut to obtain a 60mm x 120mm film. This was folded in half and one side was heat sealed with a 10mm wide seal bar at 220℃, 0.5MPa, and 3 seconds. The heat sealed portion was then cut to a width of 15mm to obtain a measurement sample (see Figure 5). The seal strength (T-type peel strength) was measured using a testing machine (manufactured by INSTRON). The test was conducted in accordance with JIS K6854 at room temperature (23℃) and a peel speed of 50mm / min. Based on the results, the following criteria were used for evaluation. The results are shown in Tables 1 and 2. A: Burst strength is 50N / 15mm or more B: Burst strength is 40N / 15mm or more and less than 50N / 15mm C: Burst strength is 35N / 15mm or more and less than 40N / 15mm D: Burst strength is less than 35N / 15mm
[0107] [High temperature seal strength] The exterior material was cut to obtain a 60mm x 120mm film. This was folded in half, and one side was heat sealed with a 10mm wide seal bar at 220°C, 0.5MPa, and 3 seconds. The heat sealed portion was cut to a width of 15mm and left to stand in a 150°C environment for 5 minutes, after which the seal strength (T-shaped peel strength, peel speed 50mm / min) was measured in a 150°C environment. Based on the results, the product was evaluated according to the following criteria. The results are shown in Tables 1 and 2. A: Burst strength is 35N / 15mm or more B: Burst strength is 30N / 15mm or more and less than 35N / 15mm C: Burst strength is 20N / 15mm or more and less than 30N / 15mm D: Burst strength is less than 20N / 15mm
[0108] [Seal strength after exposure to hydrogen sulfide (at room temperature)] The exterior material was cut to obtain a 60mm x 120mm film. This was folded in half, and one side was heat sealed with a 10mm wide seal bar at 220℃, 0.5MPa, and 3 seconds. The heat sealed portion was cut to a width of 15mm, and left to stand for 72 hours in a room temperature environment with a hydrogen sulfide concentration of 20ppm, after which the seal strength (T-shaped peel strength, peel speed 50mm / min) was measured in a room temperature environment. Based on the results, the product was evaluated according to the following criteria. The results are shown in Tables 1 and 2. A: Burst strength is 50N / 15mm or more B: Burst strength is 40N / 15mm or more and less than 50N / 15mm C: Burst strength is 35N / 15mm or more and less than 40N / 15mm D: Burst strength is less than 35N / 15mm
[0109] [Seal strength after exposure to hydrogen sulfide (150℃ environment)] The exterior material was cut to obtain a 60mm x 120mm film. This was folded in half, and one side was heat sealed with a 10mm wide seal bar at 220°C, 0.5MPa, and 3 seconds. The heat sealed portion was cut to a width of 15mm and left to stand for 72 hours in a room temperature environment with a hydrogen sulfide concentration of 20ppm. After that, it was left to stand for 5 minutes in a 150°C environment, and then the seal strength (T-shaped peel strength, peel speed 50mm / min) was measured in a 150°C environment. Based on the results, it was evaluated according to the following criteria. The results are shown in Tables 1 and 2. A: Burst strength is 35N / 15mm or more B: Burst strength is 30N / 15mm or more and less than 35N / 15mm C: Burst strength is 20N / 15mm or more and less than 30N / 15mm D: Burst strength is less than 20N / 15mm
[0110] [Table 1]
[0111] [Table 2]
[0112] In Tables 1 and 2, it can be said that the overall quality is excellent if there is no D in the evaluation results. Examples 1 to 13 were rated A to C for seal strength. In contrast, some of Comparative Examples 1 to 4 were rated D for seal strength. Specifically, Comparative Example 1 was rated D for seal strength at room temperature (initial and after hydrogen sulfide exposure). This is presumably because the temperature of the minor dispersion peak γ was higher than the range of -130°C to -50°C and the temperature of the major dispersion peak α was also higher than the range of 30°C to 130°C. Comparative Example 2 was also rated D for seal strength at room temperature (initial and after hydrogen sulfide exposure). This is presumably because the temperature of the minor dispersion peak γ was higher than the range of -130°C to -50°C. Comparative Example 3 was rated D for seal strength in a 150°C environment both before and after hydrogen sulfide exposure. This is presumably because the temperature of the minor dispersion peak γ was lower than the range of -130°C to -50°C. The seal strength of Comparative Example 4 in a 150°C environment both before and after exposure to hydrogen sulfide was also evaluated as D. This is presumably because the temperature of the minor dispersion peak γ was lower than the range of -130°C to -50°C and the temperature of the major dispersion peak α was lower than the range of 30°C to 130°C. [Explanation of symbols]
[0113] REFERENCE SIGNS LIST 10... exterior material for electricity storage device, 11... base material layer, 12... first adhesive layer, 13... barrier layer, 14... corrosion prevention treatment layer, 16... sealant layer, 16a... first resin layer, 16b... second resin layer, 16c... third resin layer, 17... second adhesive layer, 30... metal terminal, 40... resin film for terminal, 50... electricity storage device main body, 100... electricity storage device
Claims
1. A base layer; A barrier layer; A sealant layer; A laminate structure having at least the following in this order, the sealant layer has at least one minor dispersion peak γ in the range of −130° C. to −50° C. in a profile of loss tangent tan δ obtained by dynamic viscoelastic measurement under a condition of 1.0 Hz; The sealant layer comprises at least one resin selected from the group consisting of a copolymer of terephthalic acid and ethylene glycol, a copolymer of terephthalic acid and ethylene glycol and butanediol, a copolymer of terephthalic acid and isophthalic acid and ethylene glycol, butanediol and neopentyl glycol, a copolymer of terephthalic acid and ethylene glycol and 1,4-cyclohexanedimethanol, a copolymer of terephthalic acid and isophthalic acid and butanediol and hexanediol, and an amide-modified polyethylene.
2. 2. The exterior material for a storage battery device according to claim 1, wherein the sealant layer has at least one main dispersion peak α in a range of 30° C. to 130° C. in the tan δ profile.
3. The packaging material for an electricity storage device according to claim 1 or 2, wherein the sealant layer contains a plasticizer.
4. The exterior material for a storage battery device described in Claim 3, wherein the sealant layer contains at least one resin selected from the group consisting of copolymers of terephthalic acid and ethylene glycol, and copolymers of terephthalic acid with ethylene glycol and butanediol.
5. An exterior material for a storage battery device as described in claim 3 or 4, wherein the plasticizer is a glycol diester.
6. The packaging material for a power storage device according to any one of claims 1 to 5, wherein the sealant layer contains a hydrogen sulfide adsorbing substance.
7. The adhesive layer is disposed between the barrier layer and the sealant layer. The packaging material for a power storage device according to any one of claims 1 to 6, wherein the adhesive layer contains a hydrogen sulfide adsorbing substance.
8. The packaging material for a power storage device according to any one of claims 1 to 7, further comprising a corrosion prevention treatment layer provided on at least one surface of the barrier layer.
9. A method for selecting a sealant film to be used as a sealant layer in an exterior material for a storage battery device, comprising: (A) performing dynamic viscoelasticity measurement on a sealant film to be evaluated under a condition of 1.0 Hz; (B) determining whether or not at least one sub-dispersion peak γ exists in the range of −130° C. to −50° C. in the profile of tan δ obtained by the dynamic viscoelasticity measurement; Including, The sealant film comprises at least one resin selected from the group consisting of a copolymer of terephthalic acid and ethylene glycol, a copolymer of terephthalic acid and ethylene glycol and butanediol, a copolymer of terephthalic acid and isophthalic acid and ethylene glycol, butanediol and neopentyl glycol, a copolymer of terephthalic acid and ethylene glycol and 1,4-cyclohexanedimethanol, a copolymer of terephthalic acid and isophthalic acid and butanediol and hexanediol, and an amide-modified polyethylene.
10. The selection method according to claim 9, comprising the steps of: preparing a sealant film that is determined to have at least one secondary dispersion peak γ in the range of −130° C. to −50° C. in the tan δ profile; a step of bonding the sealant film and a barrier layer; The method for producing an exterior material for an electricity storage device includes the steps of:
Citation Information
Patent Citations
Plasticizer for resin and composition containing same
JP1992100836A
Outer package body for battery and battery
JP1999213965A
Button cell package
JP2001270557A
All-solid battery for household electric appliance
JP2008103292A
External facing material for power storage device
JP2013101765A
Cited By
Exterior material for power storage device and manufacturing method therefor, and method for selecting sealant film used as sealant layer in exterior material for power storage device
JP2025096422A